Experimental investigation and 1D analytical approach on convective heat transfers in engine exhaust-type turbulent pulsating flows. (25th January 2020) - Simonetti, Marco; Caillol, Christian; Higelin, Pascal; Dumand, Clément; Revol, Emmanuel
Highlights: Convective heat transfers for pulsating turbulent pipe flows are investigated. The impact of the pulsation frequency on heat transfers is studied. A heat transfer enhancement in the case of a flow in resonant conditions is observed and analyzed. Increased Nusselt number is linked to the amplitude of the velocity waveform. Abstract: The objective of the present work was to experimentally investigate flow field instantaneous characteristics and their associated heat transfer for pulsating flows representative of engine exhaust flow operating conditions. The experimental apparatus consists of a stationary turbulent hot air flow, with a variable Reynolds number, excited through a pulsating mechanism and exchanging thermal energy with a water cooled steel pipe. Pulsation frequency ranges from 10 to 95 Hz. Simultaneous time-resolved measurements of velocity and temperature were achieved by mean of coupled hot-wire anemometry and micro-unsheathed thermocouples measurements to investigate the impact of the pulsation frequency on heat transfers. Flow pulsation was found to enhance heat transfers in the entire range of frequencies. Significant improvements were observed when the flow was excited with a frequency equal to a resonant mode of the system. With the increase in velocity-amplitude ratio, an increase in the convective heat transfer was observed, with a maximum enhancement corresponding to a factor three and higher, with respect to the relative Nusselt number. Combining experimental results with an analytical formulation, derived from the 1D energy balance equation for a turbulent pulsating flow, the velocity amplitude ratio was identified as the characteristic term representative of the predominant heat-transfer enhancement mechanism.